Randomized Trial: D-Glyceric Acid Activates Mitochondrial Metabolism in 50–60-Year-Old Healthy Humans - Hirvonen, O. Petteri; Kyröläinen, Heikki; Lehti, Maarit; Kainulainen, Heikki (Frontiers in Aging, 2021)
ABSTRACT BACKGROUND: Based on earlier few studies natural metabolite D-glyceric acid (DGA) does not seem to play any role in the whole-body metabolism. Nevertheless, one ethanol oxidation related rat study with controversial results raised our interest. According to preparatory studies for regulatory approval of DGA, some highly conserved mechanisms seem to subtly activate cellular energy metabolism. Therefore present 25 days lasting double blinded human study with placebo control was initiated. PURPOSE: Main target in the present study with 30 healthy 50-60-year-old human volunteers was to find out whether an “acute” 4-day and longer 21-day exogenous DGA regimen causes subtle, well-tolerated activation of mitochondrial energy metabolism. Simultaneous target was to find out whether halved dose of DGA regimen continued to be effective in the latter part of the study. MAIN FINDINGS: The results revealed following statistically significant findings: I) plasma metabolites related to aerobic energy production, especially lactate, were strongly reduced, II) systemic inflammation was lowered both in 4- and 21-days, III) mitochondria related mRNA expressions in circulating immune cells were clearly modulated at Day4, IV) cellular membrane integrity seemed to be sharply enhanced, and V) cellular NADH/NAD+ -ratio was upregulated. CONCLUSIONS: Mitochondrial metabolism was clearly upregulated at the whole-body level in both 4- and 21-days. At the same time, the effect of DGA was surprisingly moderate. Based on received solid results, the DGA regimen may facilitate recovery from metabolic challenges like physical exercises and/or acute systemic inflammation. It may also alleviate chronic energy metabolic challenges in main organs like the liver and skeletal muscles. Enhanced membrane integrity combined with lower systemic inflammation and activated metabolic flows by the DGA regimen may be beneficial especially for the aging population.